Resident Performance of the Rapid Cardiopulmonary Assessment in the Emergency Department. Issue 6 (June 2020) - Sobolewski, Brad; Taylor, Regina G.; Geis, Gary L.; Kerrey, Benjamin T.
Abstract : Objectives: The rapid cardiopulmonary assessment (RCPA) is an essential first step in effective resuscitation of critically ill children. Pediatric residents may not be achieving competency with resuscitative skills, including RCPA. Our objective was to determine how often pediatric residents complete the RCPA for actual patients. Methods: This was an observational, cross-sectional study of senior residents (≥postgraduate year 2) performing the RCPA in the resuscitation area of a high-volume pediatric emergency department (PED), where pediatric residents are expected to perform the bedside examination and assessment for all medical (nontrauma) patients. Data were collected primarily by video review on a standard form. The primary outcome was completion of the RCPA, defined as both examination and verbalized assessment of the airway, breathing, and circulation. We explored the association between RCPA completion and both residency year and number of previous PED rotations. Results: Complete data were collected from one randomly selected patient for 71 (95%) of 75 of eligible senior residents who rotated in the PED between January and June 2013. Two residents (3%) performed a complete RCPA. Verbalized assessment of circulation was especially rare (7/71; 10%). There was no association between RCPA completion and year of training or previous PED experience ( P > 0.05). Conclusions: Senior pediatric resident performance of the RCPA in the resuscitation area of a high-volume PED was poor. There was no association between RCPA completion and greater resident experience, including in the PED. These findings add to a growing body of literature suggesting that pediatric residents are not achieving competency with the RCPA and resuscitation skills. Abstract : Supplemental digital content is available in the text.